2021
DOI: 10.1021/acs.jnatprod.1c00128
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Activity of Triterpene–Coumarin Conjugates

Abstract: A set of 12 maslinic acid–coumarin conjugates was synthesized, with 9 being maslinic acid–diamine–coumarin conjugates at the C-28 carboxylic acid group of triterpene acid and the other three being maslinic acid–coumarin conjugates at C-2/C-3 and/or C-28 of the triterpene skeleton. The cytotoxic effects of these 12 triterpene conjugates were evaluated in three cancer cell lines (B16-F10, HT29, and Hep G2) and compared, respectively, with three nontumor cell lines from the same or similar tissue (HPF, IEC-18, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Several authors have also described both MA and oleanolic acid (OA) and several of their chemical derivatives as effective compounds with antiproliferative and antiviral capacity [ 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 ]; moreover, like oleanolic acid, MA and some of its different derivatives possess antibacterial activity [ 103 ] and a potent in vitro AIDS virus protease inhibitory activity [ 104 , 105 , 106 , 132 , 138 , 139 , 140 ]. In this sense, [ 104 ] have shown that MA has a potent inhibitory effect on HIV-1 protease activity and this effect was subsequently corroborated by other groups [ 105 , 138 , 139 , 140 ].…”
Section: Biological Activities Of the Triterpenic Components Of The O...mentioning
confidence: 99%
“…Several authors have also described both MA and oleanolic acid (OA) and several of their chemical derivatives as effective compounds with antiproliferative and antiviral capacity [ 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 ]; moreover, like oleanolic acid, MA and some of its different derivatives possess antibacterial activity [ 103 ] and a potent in vitro AIDS virus protease inhibitory activity [ 104 , 105 , 106 , 132 , 138 , 139 , 140 ]. In this sense, [ 104 ] have shown that MA has a potent inhibitory effect on HIV-1 protease activity and this effect was subsequently corroborated by other groups [ 105 , 138 , 139 , 140 ].…”
Section: Biological Activities Of the Triterpenic Components Of The O...mentioning
confidence: 99%
“…In ddition to, their potent activity against human fungal pathogens such as C. tropicalis, C. albicans, and Aspergillus fumigatus. [18][19][20] Over the past few years, compounds containing thiazole and/or thiadiazole scaffold are attractive to medicinal chemistry due to their unique chemical properties and diversity of the biological activities. [20][21][22][23][24][25] Therefore, they have therapeutic effects against several diseases such as antimalarial, antimicrobial, antiproliferative agents and anti-inflammatory [26][27][28][29][30] besides their significant with various fungicidal activities .…”
Section: Introductionmentioning
confidence: 99%
“…The great attention paid by researchers to the study of coumarin derivatives is explained by their broad spectrum of biological activities including anti‐inflammatory, [17] antidiabetic, antiAlzheimer, anticancer, antioxidant, Anticonvulscent, antituberculosis, and as inhibitors of SARS‐CoV‐2 (COVID‐19) virus. In ddition to, their potent activity against human fungal pathogens such as C. tropicalis, C. albicans, and Aspergillus fumigatus [18–20] …”
Section: Introductionmentioning
confidence: 99%
“…Numerous chemical groups are being used in the synthesis of chemical derivatives of the most important triterpenoids in order to select derivatives that present a significant increase in efficiency in their bioactivity. Among them, acyl, aminoacyl, and dipeptidyl groups [ 26 , 27 , 41 , 42 ], pegylated and pegylated diamine derivatives [ 43 , 44 , 45 , 46 ], and even coumarin conjugates [ 47 ] stand out. In all cases, the anticancer, anti-inflammatory, antioxidant, or antiviral effects originally present in the molecules from which they are obtained are significantly increased.…”
mentioning
confidence: 99%